Fast Diagnostics of Urinary Tract Infections in Children using Dipsticks - Tomasik, Jan; Tomasik, Przemysław (International Journal of Child Health and Nutrition, 2022)
This article presents a practical approach to the preliminary diagnosis of urinary tract infection in suspected children using a dipstick test for urine analysis. The urine dipstick test is considered a point of care testing, as well, in several countries, as a self-testing device or waived test. In the event that positive results are obtained, a subsequent laboratory evaluation is required. If properly performed and read, the dipstick test can become a valuable diagnostic and management tool in a primary care physician’s office. It allows the introduction of treatment and further clinical diagnosis. The test remains simple, quick, and inexpensive and should be widely used.